A Optimizing the Role of Content Creators in Building Public Engagement for the Ramadan Campaign LAZISMU East Java - Nabila Nur Aini Nabila; Hannan Az-zahra Hanna; Muhammad Rizky Wisnuwardhana; Salsabila Husna Dewanda; Ahmad Satrio Jati; Dwi Prasetyo (Universitas Negeri Surabaya, 2026)
In the midst of an overwhelming digital surge, the success of philanthropic campaigns heavily relies on how messages are crafted to resonate with both the emotions and logic of the audience. This research aims to analyze the optimal role of content creators in strengthening public engagement during the Ramadan campaign spearheaded by LAZISMU East Java. The primary focus of this study is to delve into how content creators execute their strategic tasks, ranging from ideation to content distribution, utilizing the AIDCA model (Attention, Interest, Desire, Conviction, and Action). A qualitative descriptive method with a case study approach was employed. Data collection was conducted through observations of digital activities, documentation of campaign content, and a reflective analysis of the team's creative workflow. The findings indicate that content creators at LAZISMU East Java function not merely as visual technicians, but as communication intermediaries bridging humanitarian values (muzakki) with the needs of beneficiaries (mustahik). The optimization of this role is evident in their ability to transform monotonous zakat narratives into innovative content that aligns with social media trends, effectively boosting public interaction and direct donations throughout the month of Ramadan.